Multiphase modeling of tsunami impact on building with openings. (June 2016) - Ghosh, D; Mittal, AK; Bhattacharyya, SK
The estimation of wave pressure on structures is complex during tsunami due to its unpredictable velocity and direction which depends on various ocean parameters. In this context, some tsunami mitigation strategy can be adopted, so that damage to structures during tsunami may be minimized. The effectiveness of different opening sizes in buildings to reduce wave pressure is investigated numerically in the present study. These results may also be applicable to simulate the tsunami impact on breakaway wall of a building. The effectiveness in tsunami force reduction is quantified in terms of pressure reduction throughout the building height. Computational fluid dynamics technique is used to analyze the wave impact on buildings. Solitary wave is generated in numerical platform by controlling discharge in a channel inlet. Three-dimensional Reynolds Averaged Navier–Stokes model is used to solve the governing equitation of fluid flow. Realizable k–ɛ turbulence model is applied for turbulence modeling. Multiphase volume of fluid modeling technique is adopted to track the free surface movement and air–water interaction. The tsunami wave characteristics are validated against the internationally reported results. Two types of wave conditions are considered in the study to evaluate the dependence between wave height and pressure on building.